Pole piece, secondary battery, and electronic device
By using composite fiber materials in lithium-ion battery electrodes and controlling the angle and ratio of conductive agents and binders, the problem of uneven dispersion of conductive agents was solved, improving the kinetics and cycle performance of the battery and enhancing electron transport and cohesion.
Patent Information
- Application Number
- CN202510737759.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-06-04
AI Technical Summary
In the dry preparation process of lithium-ion battery electrodes, the difficulty in dispersing the conductive agent leads to an uneven electronic conductive network, which affects the kinetic performance and cycle performance of the secondary battery.
Composite fiber materials, including fibrous conductive agents and fibrous binders, are used. The included angle θ is controlled to be 0°≤θ≤60°, and the ratio A of fibrous conductive agents to fibrous binders in the material layer is maintained at 60%≤A≤100%. Uniform dispersion is achieved through a high-speed shear fiberization process to construct a good electronic conductive network.
It improves the uneven dispersion of conductive agent in the electrode material layer, enhances the kinetic and cycle performance of the secondary battery, strengthens the electron transport rate and the cohesion of the material layer, reduces polarization, and extends the battery's lifespan.
Smart Images

Figure CN120690810B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical technology, and in particular to an electrode, a secondary battery, and an electronic device. Background Technology
[0002] Secondary batteries, such as lithium-ion batteries, are widely used in smartphones, wearable devices, consumer drones, and electric vehicles due to their high energy density, long cycle life, and lack of memory effect. Dry-processing of lithium-ion battery electrodes has attracted significant attention due to its advantages such as low manufacturing cost and environmental friendliness, as it eliminates the need for solvents. However, the direct mixing of dry powders without solvents during preparation can lead to difficulties in dispersing the conductive agents in the electrodes, resulting in agglomeration and uneven distribution of the electronic conductive network within the material layer. This, in turn, affects the kinetic and cycle performance of the lithium-ion battery. Summary of the Invention
[0003] The purpose of this application is to provide an electrode, a secondary battery, and an electronic device to improve the kinetic and cycle performance of the secondary battery. The specific technical solution is as follows:
[0004] The first aspect of this application provides an electrode comprising a current collector and a material layer disposed on at least one surface of the current collector. The material layer comprises a composite fiber material, which includes a fibrous conductive agent and a fibrous binder. The fibrous conductive agent and the fibrous binder in contact with each other form an angle θ along their respective length directions, where 0° ≤ θ ≤ 60°. In any region of the material layer, the ratio of the number of fibrous conductive agents with θ ranging from 0° to 20° to the total number of fibrous conductive agents in that region is A, where 60% ≤ A ≤ 100%. The electrode of this application satisfies the above characteristics, which can improve the problem of uneven dispersion of conductive agents in the electrode material layer, reduce the agglomeration of conductive agents, and construct a good electronic conductivity network in the material layer, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0005] In some embodiments of this application, 0° ≤ θ ≤ 45°. A θ value within this range is beneficial for further improving the kinetic and cycle performance of the secondary battery.
[0006] In some embodiments of this application, 80% ≤ A ≤ 100%. A value within the above range is beneficial for further improving the kinetic and cycle performance of the secondary battery.
[0007] In some embodiments of this application, the length of the fibrous conductive agent is L1 μm, the diameter of the fibrous conductive agent is D1 nm, the length of the fibrous binder is L2 μm, and the diameter of the fibrous binder is D2 nm. The composite fiber material satisfies at least one of the following characteristics: (1) 1 ≤ L1 ≤ 30; (2) 1.5 ≤ D1 ≤ 100; (3) 5 ≤ L2 ≤ 200; (4) 10 ≤ D2 ≤ 200; (5) 3 ≤ L2 / L1 ≤ 50; (6) 0.5 ≤ D2 / D1 ≤ 100. The composite fiber material satisfies the above characteristics, which is beneficial to improving the kinetic performance and cycle performance of the secondary battery.
[0008] In some embodiments of this application, the fibrous conductive agent includes at least one of carbon nanotubes or carbon fibers, and the fibrous binder includes at least one of polytetrafluoroethylene, polytetrafluoroethylene-perfluorosulfonate copolymer, sericin, or polyacrylonitrile. Using the above-mentioned fibrous conductive agent and fibrous binder is beneficial for improving the kinetic performance and cycle performance of the secondary battery.
[0009] In some embodiments of this application, the mass percentage of the composite fiber material is 2.5% to 10% based on the mass of the material layer. By controlling the mass percentage of the composite fiber material within the above range, the secondary battery exhibits high initial coulombic efficiency and energy density, while also demonstrating good kinetic and cycle performance.
[0010] In some embodiments of this application, the mass ratio of the fibrous conductive agent to the fibrous binder is (0.1 to 1):1. By adjusting the mass ratio of the fibrous conductive agent to the fibrous binder within the above range, the fibrous conductive agent and the fibrous binder work synergistically, which is beneficial to improving the kinetic performance and cycle performance of the secondary battery.
[0011] In some embodiments of this application, the electrode sheet satisfies at least one of the following characteristics: (1) the electrode sheet includes a positive electrode sheet and a negative electrode sheet, wherein the film resistance of the positive electrode sheet is 1Ω to 5Ω and the film resistance of the negative electrode sheet is 0.001Ω to 0.05Ω; (2) the film resistance of any electrode sheet of the same area taken perpendicular to the thickness direction varies from 1% to 3.5%; (3) the film resistivity varies from 1% to 3.5% along the thickness direction of the electrode sheet. The electrode sheet satisfies the above characteristics, resulting in a higher electron transport rate in the material layer, which is beneficial for improving the kinetic performance and cycle performance of the secondary battery.
[0012] In some embodiments of this application, the cohesive force of the material layer is between 20 N / m and 100 N / m. A cohesive force within this range is beneficial for improving the kinetic and cycle performance of the secondary battery.
[0013] The second aspect of this application provides a secondary battery that includes the electrode provided in the first aspect of this application. The secondary battery of this application has good kinetic performance and cycle performance.
[0014] A third aspect of this application provides an electronic device that includes the secondary battery provided in the second aspect of this application. The electronic device of this application has a long service life and good performance.
[0015] The beneficial effects of this application are:
[0016] This application provides an electrode, a secondary battery, and an electronic device. The electrode includes a current collector and a material layer disposed on at least one surface of the current collector. The material layer includes a composite fiber material comprising a fibrous conductive agent and a fibrous binder. The fibrous conductive agent and the fibrous binder in contact with each other form an angle θ along their respective length directions, where 0° ≤ θ ≤ 60°. In any region of the material layer, the ratio of the number of fibrous conductive agents with θ ranging from 0° to 20° to the total number of fibrous conductive agents in that region is A, where 60% ≤ A ≤ 100%. The electrode of this application satisfies the above characteristics, which can improve the problem of uneven dispersion of conductive agents in the electrode material layer, reduce the agglomeration of conductive agents, and construct a good electronic conductivity network in the material layer, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0017] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.
[0019] Figure 1 This is a schematic diagram of the material layer structure along the thickness direction of one embodiment of this application.
[0020] Reference numerals: Material layer 100, composite fiber material 110, fibrous conductive agent 111, fibrous binder 112, electrode active material 120. Detailed Implementation
[0021] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0022] It should be noted that, in the specific embodiments of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries in this application are not limited to lithium-ion batteries.
[0023] In the dry preparation process of electrodes, the direct mixing of dry powders without solvents can easily lead to difficulties in dispersing the conductive agent, resulting in agglomeration. This causes uneven distribution of the electronic conductive network in the material layer, leading to poor kinetic and cycle performance of the secondary battery. Currently, while increasing the mass percentage of the conductive agent in the material layer can improve the electronic conductive network and increase the conductive channels, this also reduces the content of active electrode material, affecting the energy density of the secondary battery. Furthermore, it exacerbates the agglomeration of the conductive agent, further unevenly distributing the electronic conductive network in the material layer, and reduces the porosity of the material layer, affecting lithium-ion transport and thus impacting the kinetic and cycle performance of the secondary battery.
[0024] Based on this, a first aspect of this application provides an electrode comprising a current collector and a material layer disposed on at least one surface of the current collector. The material layer comprises a composite fiber material, which includes a fibrous conductive agent and a fibrous binder. The fibrous conductive agent and the fibrous binder in contact with each other form an angle θ along their respective length directions, where 0° ≤ θ ≤ 60°, preferably 0° ≤ θ ≤ 45°. For example, the value of θ can be 0°, 5°, 10°, 15°, 20°, 25°, 30°, 35°, 40°, 45°, 50°, 55°, 60°, or a range consisting of any two of these values. In any region of the material layer, the ratio of the number of fibrous conductive agents satisfying θ = 0° to 20° to the total number of fibrous conductive agents in that region is A, where 60% ≤ A ≤ 100%, preferably 80% ≤ A ≤ 100%. For example, the value of A can be 60%, 65%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 100%, or a range of any two of these values.
[0025] The fibrous binder and fibrous conductive agent of this application can be combined due to their high surface energy characteristics. By combining the fibrous conductive agent and fibrous binder and applying them to the electrode, and adding the fibrous conductive agent and binder simultaneously during the electrode preparation process, the fibrous conductive agent will be uniformly dispersed in the material layer during the high-speed shear fibrosis process of the binder. This ensures that the θ value and A value are within the aforementioned range, which can improve the problem of uneven dispersion of conductive agent in the electrode material layer, reduce the agglomeration of conductive agent, and make the components in the material layer uniformly distributed. This constructs a good and uniform electronic conductive network and bonding network in the material layer, which is beneficial to improving the electron transport rate, making the lithium insertion / extraction reaction rate inside the material layer more uniform, reducing polarization, and also helps to make the material layer have a suitable porosity, thereby improving the lithium ion transport rate in the material layer. At the same time, the electrode has good processability, and the cohesion of the material layer and the adhesion between the material layer and the current collector are high, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0026] When the value of θ is too large, for example, greater than 60°, the fibrous conductive agent and fibrous binder are not added separately during the preparation of the electrode. The fibrous conductive agent cannot be uniformly dispersed in the material layer during the high-speed shearing and fibrous process of the binder. The range of θ value is very large. Alternatively, the degree of combination between the fibrous conductive agent and the fibrous binder is low, and some fibrous conductive agents are not combined with the binder or the degree of combination is low. In the above cases, the conductive agent in the material layer is unevenly dispersed and prone to agglomeration, resulting in uneven distribution of the electronic conductive network. This leads to a lower electrochemical reaction rate of the electrode active material in areas with poor conductivity within the material layer, uneven lithium insertion / extraction reaction rate within the material layer, excessive polarization, and a lower lithium ion transport rate in the material layer. This is not conducive to improving the kinetic performance and cycle performance of the secondary battery. When the value of A is too small, for example, less than 60%, the fibrous conductive agent and fibrous binder are not added separately during the preparation of the electrode. The fibrous conductive agent cannot be uniformly dispersed in the material layer during the high-speed shearing and fibrous process of the binder. Alternatively, the degree of combination between the fibrous conductive agent and the fibrous binder is low, and some fibrous conductive agents are not combined with the binder or the degree of combination is low. In the above cases, the conductive agent in the material layer is unevenly dispersed and prone to agglomeration, resulting in an uneven distribution of the electronic conductive network. This leads to a lower electrochemical reaction rate of the electrode active material in areas with poor conductivity within the material layer, uneven lithium insertion / extraction reaction rate within the material layer, excessive polarization, and a lower lithium ion transport rate in the material layer. This is detrimental to improving the kinetic performance and cycle performance of the secondary battery.
[0027] For example, the length direction of the material layer is defined as X, and its width direction as Y. The material layer typically has a long side and a short side, and the aforementioned length direction refers to the extension direction of the long side of the material layer. It should be understood that the above definitions of directions are for the convenience of describing this application. Figure 1 As shown, the material layer 100 includes a composite fiber material 110 and an electrode active material 120. The composite fiber material 110 includes a fibrous conductive agent 111 and a fibrous binder 112. The fibrous conductive agent 111 and the fibrous binder 112, which are in contact with each other, have an angle of θ along their respective length directions.
[0028] In some embodiments of this application, the length of the fibrous conductive agent is L1 μm, where 1 ≤ L1 ≤ 30. For example, the value of L1 can be 1, 3, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, or a range of any two of these values. A value of L1 within the above range is beneficial for constructing a good electronic conductive network in the material layer, improving the electron transport rate, reducing the polarization of the electrode during lithium insertion / extraction reactions, and is easy to implement in the process, thereby improving the kinetic and cycle performance of the secondary battery.
[0029] In some embodiments of this application, the diameter of the fibrous conductive agent is D1 nm, where 1.5 ≤ D1 ≤ 100. For example, the value of D1 can be 1.5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, or a range of any two of these values. A D1 value within the above range is beneficial for constructing a good electronic conductive network in the material layer, improving the electron transport rate, reducing polarization during lithium insertion / extraction reactions on the electrodes, and is easy to implement in the process, thereby improving the kinetic and cycle performance of the secondary battery.
[0030] In some embodiments, the length of the fibrous conductive agent is L1 μm, the diameter of the fibrous conductive agent is D1 nm, and 0.01 ≤ L1 / D1 ≤ 20. For example, the value of L1 / D1 can be 0.01, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, or a range of any two of these values. A value of L1 / D1 within the above range is beneficial for improving the kinetic and cycle performance of the secondary battery.
[0031] In some embodiments of this application, the length of the fibrous binder is L2 μm, where 5 ≤ L2 ≤ 200. For example, the value of L2 can be 5, 30, 50, 70, 90, 100, 120, 140, 150, 160, 180, 200, or a range of any two of these values. When the value of L2 is within the above range, the fibrous binder has high mechanical strength, which is beneficial for improving the cohesion of the material layer and the adhesion between the material layer and the current collector, reducing the risk of powder shedding or peeling of the material layer from the current collector, and is easy to implement in the process, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0032] In some embodiments of this application, the diameter of the fibrous binder is D² nm, where 10 ≤ D² ≤ 200. For example, the value of D² can be 10, 30, 50, 70, 90, 100, 120, 140, 150, 160, 180, 200, or a range of any two of these values. When the value of D² is within the above range, the fibrous binder has high mechanical strength, which is beneficial for improving the cohesion of the material layer and the adhesion between the material layer and the current collector, reducing the risk of powder shedding or peeling of the material layer from the current collector, and is easy to implement in the process, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0033] In some embodiments, the length of the fibrous binder is L² μm, the diameter of the fibrous binder is D² nm, and 0.025 ≤ L² / D² ≤ 20. For example, the value of L² / D² can be 0.025, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, or a range of any two of these values. A value of L² / D² within the above range is beneficial for improving the kinetic and cycle performance of the secondary battery.
[0034] In some embodiments of this application, the length of the fibrous conductive agent is L1 μm, the length of the fibrous binder is L2 μm, and 3 ≤ L2 / L1 ≤ 50. For example, the value of L2 / L1 can be 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, or a range of any two of these values. When the value of L2 / L1 is within the above range, the fibrous conductive agent and the fibrous binder work synergistically to facilitate the construction of a good electronic conductive network in the material layer, improve the electron transport rate, reduce the polarization of the electrode during lithium insertion / extraction reactions, and simultaneously increase the cohesion of the material layer and the adhesion between the material layer and the current collector, which helps reduce the risk of powder shedding or peeling from the current collector. Furthermore, the process is easy to implement, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0035] In some embodiments of this application, the diameter of the fibrous conductive agent is D1 nm, the diameter of the fibrous binder is D2 nm, and 0.5 ≤ D2 / D1 ≤ 100. For example, the value of D2 / D1 can be 0.5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, or a range of any two of these values. When the value of D2 / D1 is within the above range, the fibrous conductive agent and the fibrous binder work synergistically to facilitate the construction of a good electronic conductive network in the material layer, improve the electron transport rate, reduce the polarization of the electrode during lithium insertion / extraction reactions, and simultaneously increase the cohesion of the material layer and the adhesion between the material layer and the current collector, which helps reduce the risk of powder shedding or peeling from the current collector. Furthermore, the process is easy to implement, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0036] In some embodiments of this application, the fibrous conductive agent includes at least one of carbon nanotubes or carbon fibers. The carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes, and the carbon fibers may include, but are not limited to, vapor-grown carbon fibers (VGCF) and / or carbon nanofibers. The fibrous binder includes at least one of polytetrafluoroethylene (PTFE), PTFE-perfluorosulfonate copolymer, sericin, or polyacrylonitrile. Using the above-mentioned fibrous conductive agent and fibrous binder is beneficial for improving the kinetic performance and cycle performance of the secondary battery.
[0037] In some embodiments of this application, the mass percentage of the composite fiber material is between 2.5% and 10% based on the mass of the material layer. For example, the mass percentage of the composite fiber material can be 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any two of these values. By controlling the mass percentage of the composite fiber material within the above range, a higher mass percentage of the electrode active material in the material layer results in a higher initial coulombic efficiency and energy density for the secondary battery. This also facilitates the construction of a good bonding network within the material layer, improving the cohesion of the material layer and the adhesion between the material layer and the current collector, leading to the preparation of a self-supporting material layer film, improving the processing performance of the electrode sheet, and further facilitating the construction of a good electronic conductivity network within the material layer. This increases the electron transport rate, improves the lithium insertion / extraction reaction rate of the electrode active material, and reduces polarization, thereby improving the kinetic and cycle performance of the secondary battery.
[0038] In some embodiments of this application, the mass ratio of the fibrous conductive agent to the fibrous binder is (0.1 to 1):1. For example, the mass ratio of the fibrous conductive agent to the fibrous binder can be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, or a range consisting of any two of these values. By adjusting the mass ratio of the fibrous conductive agent to the fibrous binder within the above range, the fibrous conductive agent and the fibrous binder work synergistically. The fibrous conductive agent coats the fibrous binder less, which is beneficial for the binding effect of the fibrous binder. This results in the formation of a good bonding network in the material layer, improving the cohesion of the material layer and the adhesion between the material layer and the current collector. At the same time, the electronic conductive network in the material layer is good and uniform, which is beneficial for electron transport, increasing the lithium insertion / extraction reaction rate of the electrode active material, reducing polarization, and thus improving the kinetic performance and cycle performance of the secondary battery.
[0039] In some embodiments, the mass percentage of the fibrous conductive agent can be from 0.23% to 5%, and the mass percentage of the fibrous binder can be from 1.25% to 9.1%, depending on the mass of the material layer. For example, the mass percentage of the fibrous conductive agent can be 0.23%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range of any two of these values, and the mass percentage of the fibrous binder can be 1.25%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9.1%, or a range of any two of these values.
[0040] In some embodiments of this application, the electrode includes a positive electrode and a negative electrode. The film resistance of the positive electrode is from 1Ω to 5Ω, and the film resistance of the negative electrode is from 0.001Ω to 0.05Ω. For example, the film resistance of the positive electrode can be 1.0Ω, 1.5Ω, 2.0Ω, 2.5Ω, 3.0Ω, 3.5Ω, 4.0Ω, 4.5Ω, 5.0Ω, or any range of two such values, and the film resistance of the negative electrode can be 0.001Ω, 0.005Ω, 0.010Ω, 0.015Ω, 0.020Ω, 0.025Ω, 0.030Ω, 0.035Ω, 0.040Ω, 0.045Ω, 0.050Ω, or any range of two such values. When the film resistance of the electrode is within the above range, the electron transport rate in the material layer is high, the lithium insertion / extraction reaction rate of the electrode active material is high, and the polarization is small, which is beneficial to improving the kinetic performance and cycle performance of the secondary battery.
[0041] In some embodiments of this application, when an electrode of the same area is randomly selected on a surface perpendicular to the thickness direction, the rate of change of film resistance is 1% to 3.5%. For example, the rate of change of film resistance can be 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, or a range of any two of these values. A rate of change of film resistance within the above range indicates that the fibrous conductive agent is uniformly dispersed in the material layer, the electronic conductive network in the material layer is uniformly distributed, the electron transport rate is high, the lithium insertion / extraction reaction rate within the material layer is uniform, and the polarization is small, thereby contributing to improved kinetic and cycle performance of the secondary battery.
[0042] In some embodiments of this application, the rate of change of film resistivity along the thickness direction of the electrode is from 1% to 3.5%. For example, the rate of change of film resistivity can be 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, or a range of any two of these values. A rate of change of film resistivity within the above range indicates that the fibrous conductive agent is uniformly dispersed in the material layer, the electronic conductive network in the material layer is uniformly distributed, the electron transport rate is high, the lithium insertion / extraction reaction rate within the material layer is uniform, and the polarization is small, thereby contributing to improved kinetic and cycle performance of the secondary battery.
[0043] In some embodiments of this application, the cohesive force of the material layer is between 20 N / m and 100 N / m. For example, the cohesive force of the material layer can be 20 N / m, 30 N / m, 40 N / m, 50 N / m, 60 N / m, 70 N / m, 80 N / m, 90 N / m, 100 N / m, or a range of any two of these values. A cohesive force within the above range indicates a good bonding network in the material layer, which is beneficial for improving the kinetic and cycle performance of the secondary battery.
[0044] In some embodiments, the composite fiber material in the material layer of this application can be formed by high-speed mixing and shearing fiberization of composite fiber material raw materials during the electrode preparation process. This application does not impose any particular limitation on the preparation method of the composite fiber material raw materials, as long as it achieves the purpose of this application. For example, the preparation of the composite fiber material raw materials may include, but is not limited to, the following steps: surface modification treatment of the fibrous conductive agent; specifically, the fibrous conductive agent is placed in an acid solution and stirred, and after stirring, it is washed with deionized water and dried, so that the surface of the fibrous conductive agent has hydrophilic functional groups such as -OH and -F. The surface-modified fibrous conductive agent is mixed and stirred with the raw material of the fibrous binder, so that the raw materials of the fibrous conductive agent and the fibrous binder are interwoven and combined to obtain a mixed fiber emulsion. The mixed fiber emulsion is freeze-dried to remove moisture, obtaining the composite fiber material raw material.
[0045] In some embodiments, when performing surface modification treatment on the fibrous conductive agent, the acid solution used can be a mixed acid solution of hydrofluoric acid and concentrated sulfuric acid, with a mass concentration of hydrofluoric acid of 5% to 20% and a mass concentration of concentrated sulfuric acid of 98%, and a mass ratio of hydrofluoric acid to concentrated sulfuric acid of 1:(3 to 5). When performing surface modification treatment on the fibrous conductive agent, the stirring speed can be 1000 rpm to 5000 rpm, and the time can be 6 h to 24 h. For example, the stirring speed can be 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, 5000 rpm, or any combination of two of these values, and the time can be 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, or any combination of two of these values.
[0046] In some embodiments, the weight-average molecular weight (Mw) of the fibrous binder can be 6 × 10⁻⁶. 6 Up to 1×10 7 For example, the weight-average molecular weight (Mw) of fibrous binders can be 6 × 10⁻⁶. 6 6.5×10 6 7×10 6 7.5×10 6 8×10 6 8.5×10 6 9×10 6 9.5×10 6 1×10 7 Or it can be a range consisting of any two of these values.
[0047] In some embodiments, when the surface-modified fibrous conductive agent and the fibrous binder raw materials are stirred, the stirring speed can be from 3000 rpm to 5000 rpm, and the stirring time can be from 4 h to 12 h. For example, the stirring speed can be 3000 rpm, 3200 rpm, 3500 rpm, 3800 rpm, 4000 rpm, 4200 rpm, 4500 rpm, 4800 rpm, 5000 rpm, or any combination of two of these values, and the stirring time can be 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, or any combination of two of these values.
[0048] This application does not impose any particular limitation on the preparation method of the electrode, as long as it can achieve the purpose of this application. For example, the preparation of the electrode may include, but is not limited to, the following steps: uniformly mixing electrode active material and composite fiber material raw materials to obtain a material layer dry powder; subjecting the material layer dry powder to high-speed mixing, shearing, and fiberization to obtain a fibrous material; hot-pressing the fibrous material to thin it to obtain a self-supporting membrane; and hot-pressing the self-supporting membrane with a current collector to obtain the electrode.
[0049] In some embodiments, the mixing temperature for uniformly mixing the electrode active material and the composite fiber material raw material can be from 0°C to 40°C, the mixing speed can be from 1000 rpm to 10000 rpm, and the mixing time can be from 10 min to 360 min. For example, the mixing temperature for uniformly mixing the electrode active material and the composite fiber material raw material can be 0°C, 5°C, 10°C, 15°C, 20°C, 22°C, 25°C, 28°C, 30°C, 35°C, 40°C, or a range of any two of these values, and the mixing speed can be 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 1... 0000 rpm or a range of any two of these values; the time can be 10 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 250 min, 280 min, 300 min, 330 min, 360 min or a range of any two of these values.
[0050] In some implementations, the high-speed hybrid shear fiberization temperature can be from 60°C to 120°C, the rotation speed can be from 3000 rpm to 10000 rpm, and the time can be from 10 min to 60 min. For example, the high-speed hybrid shear fiberization temperature can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or any two of these values; the rotation speed can be 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm, or any two of these values; and the time can be 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, or any two of these values. Controlling the process parameters of high-speed hybrid shear fiberization within the above range is beneficial for uniformly mixing the components of the material layer, reducing the risk of fracture of the composite fiber material, giving it higher mechanical strength, improving the cohesion of the material layer and the adhesion between the material layer and the current collector, building a good electronic conductive network in the material layer, improving the electron transport rate, and also facilitating the processing and preparation of the electrode material layer and reducing the expansion of the electrode active material, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0051] In some implementations, the hot-pressing thinning temperature can be from 80°C to 160°C, and the pressure can be from 0.1 tons to 10 tons. For example, the hot-pressing thinning temperature can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, or any combination of two of these values, and the pressure can be 0.1 tons, 0.5 tons, 1.0 tons, 2.0 tons, 3.0 tons, 4.0 tons, 5.0 tons, 6.0 tons, 7.0 tons, 8.0 tons, 9.0 tons, 10.0 tons, or any combination of two of these values. Controlling the hot-pressing thinning process parameters within the above ranges is beneficial for improving the cohesiveness of the material layer and the adhesion between the material layer and the current collector, reducing the impact of excessively high processing temperatures on the electrochemical performance of the secondary battery, thereby improving the kinetic and cycle performance of the secondary battery.
[0052] In some implementations, the temperature for hot-pressing the self-supporting diaphragm and the current collector can be from 80°C to 180°C, and the pressure can be from 0.1 tons to 10 tons. For example, the temperature for hot-pressing the self-supporting diaphragm and the current collector can be 80°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 180°C, or any combination of two of these values, and the pressure can be 0.1 tons, 0.5 tons, 1.0 tons, 2.0 tons, 3.0 tons, 4.0 tons, 5.0 tons, 6.0 tons, 7.0 tons, 8.0 tons, 9.0 tons, 10.0 tons, or any combination of two of these values.
[0053] In this application, the length L2 and diameter D2 of the fibrous binder can be controlled by adjusting the rotational speed and duration of high-speed mixing shear fiberization. For example, when other conditions remain constant, increasing the rotational speed of high-speed mixing shear fiberization increases the L2 value; decreasing the rotational speed decreases the L2 value. Similarly, when other conditions remain constant, extending the high-speed mixing shear fiberization time increases the L2 value; shortening the time decreases the L2 value. Likewise, when other conditions remain constant, increasing the rotational speed of high-speed mixing shear fiberization decreases the D2 value; decreasing the rotational speed increases the D2 value. Furthermore, when other conditions remain constant, extending the high-speed mixing shear fiberization time decreases the D2 value; shortening the time increases the D2 value. In this application, the length L2 and diameter D2 of the fibrous binder can also be controlled by adjusting the molecular weight of the fibrous binder. For example, when other conditions remain constant, increasing the molecular weight of the fibrous binder increases L2; decreasing the molecular weight decreases L2. When other conditions remain unchanged, an increase in the molecular weight of the fibrous binder leads to an increase in D2; a decrease in the molecular weight of the fibrous binder leads to a decrease in D2. The fibrous conductive agent of this application can be a commercially available fibrous conductive agent, and the required length L1 and diameter D1 of the fibrous conductive agent can be selected as needed.
[0054] In this application, the average value of θ within the region can be controlled by adjusting the concentration of the acid solution and the stirring time used in the surface modification treatment of the fibrous conductive agent. For example, when other conditions remain unchanged, increasing the concentration of the acid solution decreases the average value of θ; decreasing the concentration of the acid solution increases the average value of θ. When other conditions remain unchanged, extending the stirring time decreases the average value of θ; shortening the stirring time increases the average value of θ. The length L1 and diameter D1 of the fibrous conductive agent, the length L2 and diameter D2 of the fibrous binder, and the mass ratio of the fibrous conductive agent to the fibrous binder also affect the θ value. For example, when other conditions remain unchanged, decreasing the value of L1 increases the average value of θ; increasing the value of L1 decreases the average value of θ. When other conditions remain unchanged, decreasing the value of D1 decreases the average value of θ; increasing the value of D1 increases the average value of θ. When other conditions remain unchanged, decreasing the value of L2 increases the average value of θ; increasing the value of L2 decreases the average value of θ. When other conditions remain unchanged, decreasing the value of D2 increases the average value of θ; increasing the value of D2 decreases the average value of θ. When other conditions remain unchanged, an increase in the mass ratio of fibrous conductive agent to fibrous binder increases the average value of θ; a decrease in the mass ratio of fibrous conductive agent to fibrous binder decreases the average value of θ.
[0055] In this application, the A value can be controlled by adjusting the concentration of the acid solution and the stirring time used in the surface modification treatment of the fibrous conductive agent. For example, when other conditions remain unchanged, increasing the concentration of the acid solution increases the A value; decreasing the concentration of the acid solution decreases the A value. When other conditions remain unchanged, extending the stirring time increases the A value; shortening the stirring time decreases the A value. The length L1 and diameter D1 of the fibrous conductive agent, the length L2 and diameter D2 of the fibrous binder, and the mass ratio of the fibrous conductive agent to the fibrous binder also affect the A value. For example, when other conditions remain unchanged, decreasing the L1 value decreases the A value; increasing the L1 value increases the A value. When other conditions remain unchanged, decreasing the D1 value increases the A value; increasing the D1 value decreases the A value. When other conditions remain unchanged, decreasing the L2 value decreases the A value; increasing the L2 value increases the A value. When other conditions remain unchanged, decreasing the D2 value decreases the A value; increasing the D2 value increases the A value. When other conditions remain unchanged, an increase in the mass ratio of fibrous conductive agent to fibrous binder results in a decrease in the A value; conversely, a decrease in the mass ratio of fibrous conductive agent to fibrous binder results in an increase in the A value.
[0056] In this application, the electrode can be a positive electrode. The positive electrode includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The phrase "positive electrode material layer disposed on at least one surface of the positive current collector" means that the positive electrode material layer can be disposed on one surface of the positive current collector along its thickness direction, or on two surfaces of the positive current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of the positive current collector or only a portion of it; this application has no particular limitation, as long as the purpose of this application is achieved.
[0057] This application does not impose any particular restrictions on the positive electrode current collector, as long as it can achieve the purpose of this application. For example, it may include aluminum foil, aluminum alloy foil, or composite current collector (such as aluminum-carbon composite current collector).
[0058] The positive electrode material layer of this application includes a positive electrode active material, which comprises a substance capable of reversibly inserting and extracting active ions such as lithium ions. The positive electrode material layer can be one or more layers, and each layer in a multilayer positive electrode material layer can contain the same or different positive electrode active materials. This application does not impose any particular limitation on the positive electrode active material, as long as it can achieve the purpose of this application. For example, the positive electrode active material can include, but is not limited to, at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium manganese iron phosphate, or lithium titanate. The aforementioned lithium nickel cobalt manganese oxide can include LiNi... 0.95 Co 0.03 Mn 0.02 O2(Ni95), LiNi 0.91 Co 0.03 Mn 0.06 O2(Ni91), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 At least one of O2 (NCM111).
[0059] In some implementations, the mass percentage of the positive electrode active material is 90% to 97.5% based on the mass of the positive electrode material layer. For example, the mass percentage of the positive electrode active material can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 97.5%, or a range of any two of these values.
[0060] This application does not impose any particular limitation on the thickness of the positive electrode current collector, as long as the purpose of this application can be achieved. For example, the thickness of the positive electrode current collector can be from 6 μm to 25 μm. This application also does not impose any particular limitation on the thickness of the positive electrode material layer, as long as the purpose of this application can be achieved. For example, the thickness of a single-sided positive electrode material layer can be from 30 μm to 240 μm.
[0061] In this application, the electrode sheet can be a negative electrode sheet. The negative electrode sheet includes a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector. The phrase "the negative electrode sheet includes a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector" means that the negative electrode material layer can be disposed on one surface of the negative current collector along its thickness direction, or on two surfaces of the negative current collector along its thickness direction. It should be noted that the "surface" here can be the entire surface area of the negative current collector, or only a portion of the surface area; this application has no particular limitation, as long as the purpose of this application is achieved.
[0062] This application does not impose any particular restrictions on the negative electrode current collector, as long as it can achieve the purpose of this application. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collector. For example, the composite current collector may be lithium copper composite current collector, carbon copper composite current collector, nickel copper composite current collector, or titanium copper composite current collector, etc.
[0063] The negative electrode material layer of this application includes a negative electrode active material. This application does not impose any particular limitation on the negative electrode active material, as long as it can achieve the purpose of this application. For example, the negative electrode active material may include, but is not limited to, natural graphite, artificial graphite, mesophase microcarbon spheres, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, and spinel-structured lithiated TiO2-Li4Ti5O. 12 Or at least one of Li-Al alloys.
[0064] In some implementations, the mass percentage of the negative electrode active material is 90% to 97.5% based on the mass of the negative electrode material layer. For example, the mass percentage of the negative electrode active material can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 97.5%, or a range of any two of these values.
[0065] This application does not impose any particular restrictions on the thickness of the negative electrode material layer and the thickness of the negative electrode current collector, as long as the purpose of this application can be achieved. For example, the thickness of the single-sided negative electrode material layer can be from 20 μm to 200 μm, and the thickness of the negative electrode current collector can be from 4 μm to 20 μm.
[0066] The second aspect of this application provides a secondary battery that includes the electrode provided in the first aspect of this application. The secondary battery of this application has good kinetic performance and cycle performance.
[0067] In this application, the secondary battery includes a separator. This application does not impose any particular limitation on the separator, as long as it achieves the purpose of this application. For example, the material of the separator may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The type of separator may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane.
[0068] In some embodiments, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric or composite membrane with a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, or polyimide. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be used.
[0069] Optionally, a surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing polymers and inorganic substances.
[0070] In some embodiments, the inorganic layer comprises ceramic particles and an inorganic layer binder. This application does not particularly limit the ceramic particles; for example, the ceramic particles may include at least one of silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. This application does not particularly limit the inorganic layer binder; for example, the inorganic layer binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. In some embodiments, the polymer layer comprises a polymer, and the polymer material may include, but is not limited to, at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, or poly(vinylidene fluoride-hexafluoropropylene).
[0071] In this application, there is no particular limitation on the thickness of the separator, as long as it can achieve the purpose of this application. For example, the thickness of the separator can be from 3 μm to 20 μm.
[0072] In this application, the secondary battery also includes an electrolyte, which includes lithium salts and non-aqueous solvents.
[0073] This application does not impose any particular limitation on the lithium salt, as long as it achieves the purpose of this application. For example, the lithium salt may include, but is not limited to, at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalato)borate (LiBOB), or lithium difluoroborate. This application does not impose any particular limitation on the content of the lithium salt in the electrolyte, as long as it achieves the purpose of this application.
[0074] This application does not impose any particular restrictions on non-aqueous solvents, as long as they can achieve the purpose of this application. For example, non-aqueous solvents may include, but are not limited to, at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, or other organic solvents.
[0075] The aforementioned carbonate compounds may include, but are not limited to, at least one of chain carbonate compounds, cyclic carbonate compounds, or fluorocarbonate compounds. The aforementioned chain carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), or methyl ethyl carbonate (MEC). The aforementioned cyclic carbonate compounds may include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), or vinyl ethylene carbonate (VEC). The aforementioned fluorocarbonate compounds may include, but are not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The aforementioned carboxylic acid ester compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valproic acid lactone, or caprolactone. The aforementioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. Other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate. This application does not impose any particular limitation on the content of non-aqueous solvents in the electrolyte, as long as the purpose of this application is achieved.
[0076] The secondary battery also includes a casing for housing the positive electrode, separator, negative electrode, and electrolyte, as well as other components known in the field of secondary batteries. This application does not limit the scope of these other components. This application does not impose any particular limitation on the casing; it can be a casing known in the art, as long as it achieves the purpose of this application. For example, the casing can be a rigid casing or a flexible casing. The material of the rigid casing can be metal; this application does not limit the type of metal and can use known metal rigid casings, as long as they achieve the purpose of this application. The flexible casing can be a metal plastic film, such as aluminum-plastic film, steel-plastic film, etc.
[0077] The secondary battery described in this application is not particularly limited and may include any device in which an electrochemical reaction occurs. In some embodiments, the secondary battery may include, but is not limited to, lithium-ion secondary batteries (lithium-ion batteries), lithium polymer secondary batteries, or lithium-ion polymer secondary batteries.
[0078] The preparation process of the secondary battery described in this application is well known to those skilled in the art, and this application does not impose any particular limitations. For example, the preparation process of the secondary battery may include, but is not limited to, the following steps: stacking the positive electrode, separator, negative electrode, and separator in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly; placing the electrode assembly into a housing; injecting electrolyte into the housing and sealing it to obtain the secondary battery; or stacking the positive electrode, separator, negative electrode, and separator in sequence, and then fixing the four corners of the entire stacked structure with tape to obtain a stacked electrode assembly; placing the electrode assembly into a housing; injecting electrolyte into the housing and sealing it to obtain the secondary battery. In addition, overcurrent protection elements, conductive plates, etc., may be placed in the housing as needed to prevent the internal pressure of the secondary battery from rising and overcharging / discharging.
[0079] A third aspect of this application provides an electronic device that includes the secondary battery provided in the second aspect of this application. The electronic device of this application has a long service life and good performance.
[0080] The electronic device described in this application is not particularly limited and can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.
[0081] Example
[0082] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0083] Test methods and equipment:
[0084] θ value, A value, L1 value, D1 value, L2 value, D2 value test
[0085] After discharging the lithium-ion battery to 3V at 0.2C, the electrode sheets were disassembled. The electrodes were cleaned with dimethyl carbonate (DMC) and dried at 60℃. The surface of the electrode sheets perpendicular to its thickness direction was observed using a scanning electron microscope (SEM) at a magnification of 5000×. Five observation areas were randomly selected, each measuring 200μm × 200μm. Within each selected observation area, the angle θ between all contacting fibrous conductive agents and fibrous binders along their respective lengths was measured, obtaining the range of θ values within a single observation area. The ratio A of the number of fibrous conductive agents satisfying θ between 0° and 20° to the total number of fibrous conductive agents in that area was measured. The lengths and diameters of 10 fibrous conductive agents and 10 fibrous binders were measured, and the average values were calculated as the L1, D1, L2, and D2 values for each observation area. The union of the θ ranges within the five observation regions is taken as the final θ range; the average of the A, L1, D1, L2, and D2 values within the five observation regions is taken as the final A, L1, D1, L2, and D2 values.
[0086] Diaphragm resistance and its rate of change, and test of the rate of change of diaphragm resistivity.
[0087] After discharging the lithium-ion battery to 3V at 0.2C, the electrodes were disassembled. The electrodes were cleaned with dimethyl carbonate (DMC) and dried at 60°C. The current collector was removed from the electrodes, leaving only the material layer. This material layer was placed in a film resistance meter at a pressure of 25MPa, and the contact area between the material layer and the film was recorded as Sm. 2 The thickness of the material layer is denoted as dm. The film resistance RΩ of the electrode (including the positive and negative electrodes) is measured. The film resistivity ρ of the electrode is obtained according to ρ=R×S / d.
[0088] Five 1540.25mm² holes were punched at any location in the electrode material layer. 2 The test samples were measured using a diaphragm resistance meter at a pressure of 25 MPa, and the diaphragm resistances of the test samples were recorded as R1Ω, R2Ω, R3Ω, R4Ω, and R5Ω, respectively. The rate of change of diaphragm resistance perpendicular to the thickness direction was calculated using the following formulas: a=|R1-R| / R×100%, b=|R2-R| / R×100%, c=|R3-R| / R×100%, d=|R4-R| / R×100%, e=|R5-R| / R×100%, and the rate of change of diaphragm resistance perpendicular to the thickness direction (%)=(a+b+c+d+e) / 5.
[0089] The electrode material layer is divided into 5 equal parts according to its thickness. Using plasma electrode thinning technology, the material layer is gradually thinned from the surface downwards over a controlled time period. The thicknesses are denoted as d1 m, d2 m, d3 m, d4 m, and d5 m respectively (for example, if the material layer thickness is 30 μm, then d1 = 3 × 10⁻⁶). -5 m, d2 = 2.4 × 10 -5 m, d3 = 1.8 × 10 -5 m, d4 = 1.2 × 10 -5 m, d5=6×10 -6 Using a diaphragm resistance meter, the test pressure was 25 MPa, and the contact area between the diaphragm and the material layer was recorded as Sm. 2 The membrane resistances of the five test samples with different thicknesses were tested and denoted as R1′Ω, R2′Ω, R3′Ω, R4′Ω, and R5′Ω, respectively. The membrane resistivity was denoted as ρ1Ω·m, ρ2Ω·m, ρ3Ω·m, ρ4Ω·m, and ρ5Ω·m, respectively, and calculated using the following formulas: ρ1(Ω·m)=R1′×S / d1, ρ2(Ω·m)=R2′×S / d2, ρ3(Ω·m)=R3′×S / d3, ρ4(Ω·m)=R4′×S / d4, ρ5(Ω·m)=R5′×S / d5. The rate of change of diaphragm resistivity along the thickness direction is calculated using the following formulas: a′=∣ρ1-ρ∣ / ρ×100%, b′=∣ρ2-ρ∣ / ρ×100%, c′=∣ρ3-ρ∣ / ρ×100%, d′=∣ρ4-ρ∣ / ρ×100%, e′=∣ρ5-ρ∣ / ρ×100%, and the rate of change of diaphragm resistivity along the thickness direction (%)=(a′+b′+c′+d′+e′) / 5.
[0090] Cohesive strength test of material layer
[0091] The electrode sample was cut into test strips 20mm wide and 100mm long. A 20mm wide and 80mm long single-sided adhesive tape was centered on the electrode. A 20mm wide and 60mm long strip of paper was cut and inserted into the gap between the electrode and the single-sided adhesive tape, with an overlap length of 15mm. The test strip was rolled back and forth four times with a roller to obtain the test sample. A tensile testing machine was used. The paper strip was fixed with a clamp, and then the tensile testing machine was started to pull the paper strip at a speed of 50mm / min until the single-sided adhesive tape of the adhesive material layer separated from the electrode. The test was then stopped, and the data was saved. The cohesive force F of the material layer was calculated based on the tensile force and the tensile displacement when the single-sided adhesive tape of the adhesive material layer separated from the electrode, in N / m.
[0092] Ratio Performance Test
[0093] At 25℃, after allowing the lithium-ion battery to stand for 5 minutes, it is charged at a constant current of 0.7C to 4.53V, then charged at a constant voltage of 4.53V to 0.05C. After standing for 5 minutes, it is discharged at a constant current of 0.2C to 3.0V. The discharge capacity of the lithium-ion battery at this point is measured and recorded as the 0.2C discharge capacity. Then, after standing for 5 minutes, it is charged at a constant current of 0.7C to 4.53V, then charged at a constant voltage of 4.53V to 0.05C. After standing for 5 minutes, it is discharged at a constant current of 2C to 3.0V. The discharge capacity of the lithium-ion battery at this point is measured and recorded as the 2C discharge capacity. 2C discharge capacity / 0.2C discharge capacity (%) = 2C discharge capacity / 0.2C discharge capacity × 100%. The kinetic performance of lithium-ion batteries is characterized by the ratio of 2C discharge capacity to 0.2C discharge capacity. The larger the ratio, the better the kinetic performance of the lithium-ion battery; the smaller the ratio, the worse the kinetic performance of the lithium-ion battery.
[0094] Cyclic performance test
[0095] At 25℃, the lithium-ion battery was charged at a constant current of 0.5C to a voltage of 4.53V, then charged at a constant voltage of 4.53V to a current of 0.025C, and finally discharged at a constant current of 0.5C to a voltage of 3.0V. The discharge capacity of the lithium-ion battery at this point was measured and recorded as the discharge capacity of the first cycle. This charge-discharge cycle was then performed for 500 cycles, and the discharge capacity of the 500th cycle was measured. Cycle capacity retention (%) = Discharge capacity of the 500th cycle / Discharge capacity of the first cycle × 100%.
[0096] Example 1-1
[0097] <Preparation of raw materials for composite fiber materials>
[0098] Carbon nanotube powder was placed in a mixed acid solution of 10% hydrofluoric acid and 98% concentrated sulfuric acid, with a mass ratio of 1:4 for 10% hydrofluoric acid and 1:50 for carbon nanotube powder. The mixture was stirred at 3000 rpm for 20 hours. After stirring, the powder was washed with deionized water and dried to obtain surface-modified carbon nanotube powder. The surface-modified carbon nanotube powder was then mixed with a polytetrafluoroethylene (PTFE) emulsion (the PTFE emulsion was in deionized water as the solvent, and the PTFE content was 15 wt%, with a weight-average molecular weight Mw = 8 × 10⁻⁶). 6 The carbon nanotubes and polytetrafluoroethylene were mixed, with the mass ratio of carbon nanotubes to polytetrafluoroethylene shown in Table 2 (0.5:1 in Example 1-1), and stirred at 4000 rpm for 12 hours to obtain a mixed fiber emulsion. The mixed fiber emulsion was then freeze-dried to remove moisture, yielding the raw material for the composite fiber material.
[0099] <Preparation of Negative Electrode Sheets>
[0100] Artificial graphite (anode active material), silicon-carbon composite material (silicon to carbon ratio 1:1), and composite fiber material raw materials were added to a vacuum mixer and mixed at 2000 rpm for 30 minutes at 25°C to obtain a uniformly mixed anode material layer dry powder. The mass ratio of the anode active material artificial graphite, silicon-carbon composite material, and composite fiber material raw materials was 47.5:47.5:5. The mass ratio of fibrous conductive agent to fibrous binder in the composite fiber material raw material is shown in Table 2. The above anode material layer dry powder was added to a high-speed mixer and mixed at 4800 rpm for 30 minutes at 110°C for high-speed mixing, shearing, and fiberization. After completion, the mixture was sieved to obtain fibrous material. The fibrous material was then subjected to multiple differential hot pressing and thinning processes on hot rollers at 100°C and 5 tons to obtain a self-supporting anode membrane. A self-supporting negative electrode diaphragm is placed on one surface of an 8μm thick copper foil current collector for hot pressing at 120℃ with a pressure of 10 tons, resulting in a negative electrode sheet with a negative electrode material layer on one side. The above steps are then repeated on the other surface of the copper foil to obtain a negative electrode sheet with negative electrode material layers on both sides. After cold pressing, cutting, and welding of tabs, a negative electrode sheet with dimensions of 96mm × 1000mm is obtained for use. The thickness of the single-sided negative electrode material layer is 30μm, and the compaction density of the negative electrode material layer is 1.7g / cm³. 3 The L1, D1, L2, and D2 in the negative electrode material layer are shown in Table 1.
[0101] <Preparation of the positive electrode>
[0102] Lithium cobalt oxide (LiCoO2) and composite fiber material were added to a vacuum mixer and mixed at 2000 rpm for 30 minutes at 25°C to obtain a uniformly mixed dry powder of the positive electrode material layer. The mass ratio of lithium cobalt oxide (LiCoO2) to the composite fiber material was 95:5. The mass ratio of fibrous conductive agent to fibrous binder in the composite fiber material is shown in Table 2. The above dry powder of the positive electrode material layer was added to a high-speed mixer and mixed at 4800 rpm for 30 minutes at 110°C for high-speed mixing, shearing, and fiberization. After the process, the mixture was sieved to obtain fibrous material. The fibrous material was then subjected to multiple differential hot-pressing thinning processes on hot rollers at 100°C and 5 tons to obtain a self-supporting positive electrode membrane. The self-supporting positive electrode membrane was placed on one surface of a 13 μm thick aluminum foil current collector and hot-pressed at 120°C and 10 tons to obtain a positive electrode sheet with a positive electrode material layer on one side. The above steps are then repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with positive electrode material layers on both sides. After cold pressing, cutting, and welding of tabs, a positive electrode sheet with dimensions of 92mm × 1000mm is obtained for use. The thickness of the positive electrode material layer on one side is 64μm, and the compaction density of the positive electrode material layer is 4.3g / cm³. 3 .
[0103] <Isolation membrane>
[0104] A 7μm thick porous polyethylene polymer film (manufacturer: Celgard Diaphragm Company, USA) was used as the separator.
[0105] <Preparation of Electrolyte>
[0106] In an argon-atmospheric glove box with a water content of less than 10 ppm, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of 10:30:60 to obtain a base solvent. Lithium salt LiPF6 was then added and stirred until homogeneous to obtain the electrolyte. The total mass of the electrolyte contained 12.5% lithium salt LiPF6, with the remainder being the base solvent.
[0107] <Preparation of Lithium-ion Batteries>
[0108] The positive electrode, separator, negative electrode, and separator are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The electrode assembly is then wound to form the electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag and dehydrated at 80°C. A prepared electrolyte is then injected, followed by vacuum sealing, settling, formation, and shaping processes to obtain a lithium-ion battery. The formation upper limit voltage is 4.53V, the formation temperature is 85°C, and the formation time is 60 minutes.
[0109] Examples 1-2 to Examples 1-12
[0110] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as in Example 1-1. Among them, Examples 1-2 to 1-5 are as shown in Table 1 by adjusting the molecular weight of the fibrous binder and the process parameters (speed and time) of high-speed mixing and shearing fiberization in <Preparation of raw materials for composite fiber materials>, <Preparation of negative electrode> and <Preparation of positive electrode>; Examples 1-12 are as shown in Table 1 by adjusting the stirring time during the surface modification treatment of the fibrous conductive agent in <Preparation of raw materials for composite fiber materials>.
[0111] Examples 2-1 to 2-6
[0112] Except for adjusting the corresponding preparation parameters according to Table 2 in <Preparation of Composite Fiber Material Raw Materials>, <Preparation of Negative Electrode Sheets>, and <Preparation of Positive Electrode Sheets>, the rest are the same as in Examples 1-1. Specifically, in <Preparation of Negative Electrode Sheets>, when the mass percentage of the composite fiber material changes, the mass percentage of the negative electrode active material, artificial graphite, changes accordingly, while the mass percentage of the negative electrode active material, silicon-carbon composite material, remains unchanged.
[0113] Comparative Example 1
[0114] Except for the omission of <Preparation of Composite Fiber Material Raw Materials>, <Preparation of Negative Electrode> and <Preparation of Positive Electrode> which use the following preparation methods, the rest are the same as in Examples 1-1.
[0115] <Preparation of Negative Electrode Sheets>
[0116] Artificial graphite (anode active material), silicon-carbon composite material (silicon to carbon mass ratio 1:1), carbon nanotubes (anode conductive agent), and polytetrafluoroethylene (anode binder) were added to a vacuum mixer and mixed at 2000 rpm for 30 minutes at 25°C to obtain a uniformly mixed anode material layer dry powder. The mass ratio of the anode active material artificial graphite, silicon-carbon composite material, carbon nanotubes, and polytetrafluoroethylene was 47.5:47.5:1.7:3.3. The anode material layer dry powder was then added to a high-speed mixer and mixed at 4800 rpm for 30 minutes at 110°C for high-speed mixing, shearing, and fiberization. After the process, the mixture was sieved to obtain fibrous material. This fibrous material was then subjected to multiple differential hot-pressing thinning processes on hot rollers at 100°C and 5 tons to obtain a self-supporting anode membrane. A self-supporting negative electrode diaphragm is placed on one surface of an 8μm thick copper foil current collector for hot pressing at 120℃ with a pressure of 10 tons, resulting in a negative electrode sheet with a negative electrode material layer on one side. The above steps are then repeated on the other surface of the copper foil to obtain a negative electrode sheet with negative electrode material layers on both sides. After cold pressing, cutting, and welding of tabs, a negative electrode sheet with dimensions of 96mm × 1000mm is obtained for use. The thickness of the single-sided negative electrode material layer is 30μm, and the compaction density of the negative electrode material layer is 1.7g / cm³. 3 .
[0117] <Preparation of the positive electrode>
[0118] Lithium cobalt oxide (LiCoO2), carbon nanotubes, and polytetrafluoroethylene (PTFE) were added to a vacuum mixer and mixed at 2000 rpm for 30 minutes at 25°C to obtain a uniformly mixed dry powder of the positive electrode material layer. The mass ratio of LiCoO2, carbon nanotubes, and PTFE was 95:1.7:3.3. This dry powder was then added to a high-speed mixer and mixed at 4800 rpm for 30 minutes at 110°C for high-speed mixing, shearing, and fiberization. After the process, the mixture was sieved to obtain fibrous material. This fibrous material was then subjected to multiple differential hot-pressing thinning processes on hot rollers at 100°C and 5 tons to obtain a self-supporting positive electrode membrane. A self-supporting positive electrode diaphragm is placed on one surface of a 13μm thick aluminum foil current collector, and hot-pressed at 120℃ with a pressure of 10 tons to obtain a positive electrode sheet with a positive electrode material layer on one side. The above steps are then repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a positive electrode material layer on both sides. After cold pressing, cutting, and welding of tabs, a positive electrode sheet with dimensions of 92mm × 1000mm is obtained for use. The thickness of the single-sided positive electrode material layer is 64μm, and the compaction density of the positive electrode material layer is 4.3g / cm³.3 .
[0119] Comparative Example 2
[0120] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as in Example 1-1. Specifically, the parameters are as shown in Table 1 by adjusting the stirring time during the surface modification treatment of the fibrous conductive agent in the <Preparation of Raw Materials for Composite Fiber Materials>.
[0121] Comparative Example 3
[0122] Except for the following preparation methods used in <Preparation of Negative Electrode> and <Preparation of Positive Electrode>, the rest are the same as in Examples 1-1.
[0123] <Preparation of Negative Electrode Sheets>
[0124] Artificial graphite (anode active material), silicon-carbon composite material (silicon to carbon mass ratio 1:1), composite fiber material raw material, and carbon nanotubes were added to a vacuum mixer and mixed at 2000 rpm for 30 minutes at 25°C to obtain a uniformly mixed anode material layer dry powder. The mass ratio of the anode active material artificial graphite, silicon-carbon composite material, composite fiber material raw material, and carbon nanotubes was 47.5:47.5:4.95:0.05, and the mass ratio of fibrous conductive agent to fibrous binder in the composite fiber material raw material was 0.5:1. The above anode material layer dry powder was added to a high-speed mixer and mixed at 4800 rpm for 30 minutes at 110°C for high-speed mixing, shearing, and fiberization. After completion, the mixture was sieved to obtain fibrous material. The fibrous material was then subjected to multiple differential hot pressing thinning processes on hot rollers at a temperature of 100°C and a pressure of 5 tons to obtain a self-supporting anode membrane. A self-supporting negative electrode diaphragm is placed on one surface of an 8μm thick copper foil current collector for hot pressing at 120℃ with a pressure of 10 tons, resulting in a negative electrode sheet with a negative electrode material layer on one side. The above steps are then repeated on the other surface of the copper foil to obtain a negative electrode sheet with negative electrode material layers on both sides. After cold pressing, cutting, and welding of tabs, a negative electrode sheet with dimensions of 96mm × 1000mm is obtained for use. The thickness of the single-sided negative electrode material layer is 30μm, and the compaction density of the negative electrode material layer is 1.7g / cm³. 3 .
[0125] <Preparation of the positive electrode>
[0126] Lithium cobalt oxide (LiCoO2), composite fiber material, and carbon nanotubes were added to a vacuum mixer and mixed at 2000 rpm for 30 minutes at 25°C to obtain a uniformly mixed dry powder of the positive electrode material layer. The mass ratio of lithium cobalt oxide (LiCoO2), composite fiber material, and carbon nanotubes was 95:4.95:0.05, and the mass ratio of fibrous conductive agent to fibrous binder in the composite fiber material was 0.5:1. The above dry powder of the positive electrode material layer was added to a high-speed mixer and mixed at 4800 rpm for 30 minutes at 110°C for high-speed mixing, shearing, and fiberization. After the process, the mixture was sieved to obtain fibrous material. The fibrous material was then subjected to multiple differential hot pressing thinning processes on hot rollers at a temperature of 100°C and a pressure of 5 tons to obtain a self-supporting positive electrode membrane. A self-supporting positive electrode diaphragm is placed on one surface of a 13μm thick aluminum foil current collector, and hot-pressed at 120℃ with a pressure of 10 tons to obtain a positive electrode sheet with a positive electrode material layer on one side. The above steps are then repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a positive electrode material layer on both sides. After cold pressing, cutting, and welding of tabs, a positive electrode sheet with dimensions of 92mm × 1000mm is obtained for use. The thickness of the single-sided positive electrode material layer is 64μm, and the compaction density of the positive electrode material layer is 4.3g / cm³. 3 .
[0127] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.
[0128]
[0129]
[0130] As can be seen from Examples 1-1 to 1-12 and Comparative Examples 1 to 3, the electrode of this application, by adjusting the θ and A values within the range of this application, exhibits smaller film resistance and its rate of change, and smaller rate of change of film resistivity. This results in greater cohesion of the negative electrode material layer and higher 2C discharge capacity / 0.2C discharge capacity and cycle capacity retention of the lithium-ion battery, indicating good kinetic and cycle performance of the lithium-ion battery of this application. In contrast, the θ and / or A values of the lithium-ion batteries in Comparative Examples 1 to 3 are outside the range of this application, resulting in lower 2C discharge capacity / 0.2C discharge capacity and cycle capacity retention, indicating poor kinetic and cycle performance of the lithium-ion batteries.
[0131] The values of L1, D1, L2, D2, L2 / L1, and D2 / D1 affect the kinetic and cycle performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-11, when the values of L1, D1, L2, D2, L2 / L1, and D2 / D1 are within the range of this application, the film resistance and its rate of change, as well as the rate of change of film resistivity, are relatively small. The cohesion of the negative electrode material layer is relatively large, and the 2C discharge capacity / 0.2C discharge capacity and cycle capacity retention rate of the lithium-ion battery are relatively large, indicating that the lithium-ion battery of this application has good kinetic and cycle performance.
[0132] The mass percentage of composite fiber material affects the kinetic and cycle performance of lithium-ion batteries. As can be seen from Examples 1-1, 2-1 to 2-2, when the mass percentage of composite fiber material is within the range of this application, the film resistance and its rate of change, and the rate of change of film resistivity are relatively small, the cohesion of the negative electrode material layer is relatively large, and the 2C discharge capacity / 0.2C discharge capacity and cycle capacity retention rate of the lithium-ion battery are relatively large, indicating that the lithium-ion battery of this application has good kinetic and cycle performance.
[0133] The mass ratio of fibrous conductive agent to fibrous binder affects the kinetic and cycle performance of lithium-ion batteries. As can be seen from Examples 1-1, 2-3 to 2-4, when the mass ratio of fibrous conductive agent to fibrous binder is within the range of this application, the film resistance and its rate of change, and the rate of change of film resistivity of the electrode are relatively small, the cohesion of the negative electrode material layer is relatively large, and the 2C discharge capacity / 0.2C discharge capacity and cycle capacity retention rate of the lithium-ion battery are relatively large, indicating that the lithium-ion battery of this application has good kinetic and cycle performance.
[0134] The types of fibrous conductive agents and fibrous binders affect the kinetic and cycle performance of lithium-ion batteries. As can be seen from Examples 1-1, 2-5 to 2-6, when fibrous conductive agents and fibrous binders within the scope of this application are selected, the film resistance and its rate of change, and the rate of change of film resistivity of the electrode are relatively small, the cohesion of the negative electrode material layer is relatively large, and the 2C discharge capacity / 0.2C discharge capacity and cycle capacity retention rate of the lithium-ion battery are relatively large, indicating that the lithium-ion battery of this application has good kinetic and cycle performance.
[0135] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.
[0136] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.
[0137] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. An electrode comprising a current collector and a material layer disposed on at least one surface of the current collector, the material layer comprising a composite fiber material, the composite fiber material comprising a fibrous conductive agent and a fibrous binder, wherein the fibrous conductive agent and the fibrous binder in contact with each other form an angle θ along their respective length directions, 0°≤θ≤60°; and in any region of the material layer, the ratio of the number of fibrous conductive agents satisfying θ = 0° to 20° to the total number of fibrous conductive agents in that region is A, 60%≤A≤100%.
2. The electrode according to claim 1, wherein, 0°≤θ≤45°.
3. The electrode according to claim 1, wherein, 80%≤A≤100%。 4. The electrode according to claim 1, wherein, The fibrous conductive agent has a length of L1 μm and a diameter of D1 nm, the fibrous binder has a length of L2 μm and a diameter of D2 nm, and the composite fiber material satisfies at least one of the following characteristics: (1)1≤L1≤30; (2)1.5≤D1≤100; (3)5≤L2≤200; (4)10≤D2≤200; (5) 3≤L2 / L1≤50; (6) 0.5 ≤ D2 / D1 ≤ 100.
5. The electrode according to any one of claims 1 to 4, wherein, The fibrous conductive agent includes at least one of carbon nanotubes or carbon fibers, and the fibrous binder includes at least one of polytetrafluoroethylene, polytetrafluoroethylene-perfluorosulfonate copolymer, sericin, or polyacrylonitrile.
6. The electrode according to any one of claims 1 to 4, wherein, Based on the mass of the material layer, the mass percentage of the composite fiber material is 2.5% to 10%.
7. The electrode according to claim 6, wherein, The mass ratio of the fibrous conductive agent to the fibrous binder is (0.1 to 1):
1.
8. The electrode according to any one of claims 1 to 4, wherein, The electrode sheet satisfies at least one of the following characteristics: (1) The electrode includes a positive electrode and a negative electrode, wherein the film resistance of the positive electrode is 1Ω to 5Ω and the film resistance of the negative electrode is 0.001Ω to 0.05Ω; (2) When the same area of the electrode is randomly selected on the surface perpendicular to the thickness direction, the rate of change of the film resistance is 1% to 3.5%; (3) Along the thickness direction of the electrode, the rate of change of the film resistivity is 1% to 3.5%.
9. The electrode according to any one of claims 1 to 4, wherein, The cohesive strength of the material layer is 20 N / m to 100 N / m.
10. A secondary battery comprising the electrode sheet according to any one of claims 1 to 9.
11. An electronic device comprising the secondary battery of claim 10.
Citation Information
Patent Citations
Flexible fibrous knittable lithium ion battery negative electrode as well as preparation and application thereof
CN115172750A
Positive pole piece and secondary battery
CN118173788A
